Simulating oil palm expansion requires credible approaches that address real issues - Dudley, R.G.; Sheil, Douglas; Colfer, C.J.P. (2008)
Although we approve of their goals, we have significant concerns about both the technical accuracy and local understanding revealed in Sandker et al. (2007). One value of modeling, as the authors indicate, is to help stimulate debate about important, complex issues. Debate is enhanced because a well-structured model explicitly states the assumptions concerning causal relationships among its components. Genuine participation by domain experts and stakeholders helps ensure that these relationships reflect an accepted, although simplified, reality. If model structure is unduly complicated, unclear, or inaccessible, such debate will be limited. One advantage of system dynamics modeling is that, over the past 50 years, a fairly standardized approach has evolved that, if used, encourages effective communication regarding model structure, assumptions, and outcomes. For a complete treatment of this approach, see Sterman (2000). In addition to using a standardized approach and software (e.g., Stella®, Vensim®, PowerSim®, and similar packages, some with free versions), the system dynamics paradigm also provides model evaluation tools and verification protocols (e.g., Barlas 1996, Sterman 2000, Chapter 21). These help ensure the overall value and utility of a model. This matters because the desired end product is not the model, but improved scientific understanding and policy formulation.